Ultra-high-b-value kurtosis imaging for noninvasive tissue characterization of ovarian lesions - Mokry, Theresa; Młynarska-Bujny, Anna; Kuder, Tristan Anselm; Hasse, Felix; Hog, Robert; Wallwiener, Markus; Dinkic, Christine; Brucker, Janina; Sinn, Peter; Gnirs, Regula; Kauczor, Hans-Ulrich; Schlemmer, Heinz-Peter; et al. (Radiology, 2020)
Background MRI with contrast material enhancement is the imaging modality of choice to evaluate sonographically indeterminate adnexal masses. The role of diffusion-weighted MRI, however, remains controversial. Purpose To evaluate the diagnostic performance of ultra-high-b-value diffusion kurtosis MRI in discriminating benign and malignant ovarian lesions. Materials and Methods This prospective cohort study evaluated consecutive women with sonographically indeterminate adnexal masses between November 2016 and December 2018. MRI at 3.0 T was performed, including diffusion-weighted MRI (b values of 0-2000 sec/mm2). Lesions were segmented on b of 1500 sec/mm2 by two readers in consensus and an additional independent reader by using full-lesion segmentations on a single transversal slice. Apparent diffusion coefficient (ADC) calculation and kurtosis fitting were performed. Differences in ADC, kurtosis-derived ADC (Dapp), and apparent kurtosis coefficient (Kapp) between malignant and benign lesions were assessed by using a logistic mixed model. Area under the receiver operating characteristic curve (AUC) for ADC, Dapp, and Kapp to discriminate malignant from benign lesions was calculated, as was specificity at a sensitivity level of 100%. Results from two independent reads were compared. Histopathologic analysis served as the reference standard. Results A total of 79 ovarian lesions in 58 women (mean age ± standard deviation, 48 years ± 14) were evaluated. Sixty-two (78%) lesions showed benign and 17 (22%) lesions showed malignant histologic findings. ADC and Dapp were lower and Kapp was higher in malignant lesions: median ADC, Dapp, and Kapp were 0.74 µm2/msec (range, 0.52-1.44 µm2/msec), 0.98 µm2/msec (range, 0.63-2.12 µm2/msec), and 1.01 (range, 0.69-1.30) for malignant lesions, and 1.13 µm2/msec (range, 0.35-2.63 µm2/msec), 1.45 µm2/msec (range, 0.44-3.34 µm2/msec), and 0.65 (range, 0.44-1.43) for benign lesions (P values of .01, .02, < .001, respectively). AUC for Kapp of 0.85 (95% confidence interval: 0.77, 0.94) was higher than was AUC from ADC of 0.78 (95% confidence interval: 0.67, 0.89; P = .047). Conclusion Diffusion-weighted MRI by using quantitative kurtosis variables is superior to apparent diffusion coefficient values in discriminating benign and malignant ovarian lesions and might be of future help in clinical practice, especially in patients with contraindication to contrast media application. © RSNA, 2020 Online supplemental material is available for this article.
Gesehen am 02.09.2020